Coastal aquaculture, mangrove deforestation and blue carbon emissions: Is REDD+ a solution?. (April 2016) - Ahmed, Nesar; Glaser, Marion
Abstract: Globally, coastal aquaculture particularly shrimp farming has been under huge criticism because of its environmental impacts including devastating effects on mangrove forests. However, mangroves are ecologically and economically important forests, and the most carbon- rich forests in the tropics that provide a wide range of ecosystem services and biodiversity conservation. Carbon emissions are likely to have been the dominant cause of climate change and blue carbon emissions are being critically augmented through mangrove deforestation. Because of mangrove deforestation, different climatic variables including coastal flooding, cyclone, drought, rainfall, salinity, sea- level rise, and sea surface temperature have dramatic effects on coastal aquaculture. Mangrove forests have been instrumental in augmenting resilience to climate change. The "Reducing Emissions from Deforestation and forest Degradation (REDD)" program can help to restore mangroves which in turn increases options for adaptation to climate change. However, technical and financial assistance with institutional support are needed to implement REDD+. Highlights: Coastal aquaculture has devastating effects on mangrove forests. Mangroves are the most carbon- rich forests in the tropics. Blue carbon emissions are being critically augmented through mangrove deforestation. Different climatic variables have dramatic effects on coastal aquaculture. The REDD+ program can help to restore mangrove forests.